Sudden shift to remote genetic counseling during the COVID‐19 pandemic: Experiences of genetics professionals in Italy. Issue 4 (6th June 2021) - Turchetti, Daniela; Battistuzzi, Linda; Bertonazzi, Benedetta; Godino, Lea
Abstract: The 2020 COVID‐19 pandemic has rendered in‐person provision of genetic counseling impossible for prolonged periods in many countries, mandating a sudden shift to remote delivery. We used qualitative thematic analysis to explore Italian genetics professionals' experience with remote genetic counseling. Fourteen group and four individual interviews were conducted after participants had delivered one or more remote sessions via videoconference or on the telephone. Data were coded and grouped under themes. Three main themes were identified as follows: (a) technical and logistical issues, (b) communication issues, and (c) clinical content and outcome of the session. The participants acknowledged that not having to travel to the clinic saves consultands time and expense. They also highlighted that not sharing a physical space with consultands and having to rely on technology can negatively impact on effective communication, building trusting relationships, and performing accurate psychosocial assessments. Regarding the clinical content of sessions, remote genetic counseling was perceived to favor greater focus and succinct, to the point communication. However, participants also felt uncomfortable not being able to use visual aids to support the explanation of complex concepts. Moreover, demographics and the socio‐cultural status of consultands emerged as factors influencing the outcome of remote genetic counseling sessions. Finally, participants reported feeling that more experience with this novel approach would improve their confidence and their ability to adapt their counseling skills as appropriate. Based on these findings, we suggest that effective, equitable provision of remote genetic counseling will require an infrastructure that is able to support video counseling, sharing of clinical documents and visual aids, and connect with a wide range of devices. Moreover, the structure of sessions should be tailored to the specific requirements of remote genetic counseling and suitable training efforts should be promoted to enhance professionals' communication skills.